Electronic Structure and Magnetic Properties of Double Perovskites Ca2MnIrO6 (BIBECHANA, 2022)
Using the density functional theory formalism, electronic and magnetic properties of double perovskites Ca2MnIrO6  are investigated. We found ferrimagnetic ground state with half-metallic nature in Ca2MnIrO6. The electron-correlation, crystal distortion, and spin-orbit coupling (SOC) plays significant role in dictating the electronic properties in this system. From the density of states calculations, a strong hybridization were noted between O-2p, Ir-5d and Mn-3d states resulting Ca2MnIrO6 to half-metal (HM) with metallic state in spin up channel and insulating state in spin-down channel.  The HM state persists even when SOC is taken into account, though the spin-polarization reduces slightly. We thus predict Ca2MnIrO6  as a new HM ferrimagnet which can be useful for modern technological applications. We further investigated the Curie temperature of Ca2MnIrO6  by calculating the spin-exchange coupling parameters. Our results are found to be comparable with other perovskites.BIBECHANA 19  (2022) 127-132